Survey of the Applications of NGS to Whole-Genome Sequencing and Expression Profiling - Lim, Jong-Sung (Korea Genome Organization, 2012)
Recently, the technologies of DNA sequence variation and gene expression profiling have been used widely as approaches in the expertise of genome biology and genetics. The application to genome study has been particularly developed with the introduction of the next-generation DNA sequencer (NGS) Roche/454 and Illumina/Solexa systems, along with bioinformation analysis technologies of whole-genome de novo assembly, expression profiling, DNA variation discovery, and genotyping. Both massive whole-genome shotgun paired-end sequencing and mate paired-end sequencing data are important steps for constructing de novo assembly of novel genome sequencing data. It is necessary to have DNA sequence information from a multiplatform NGS with at least 2× and 30× depth sequence of genome coverage using Roche/454 and Illumina/Solexa, respectively, for effective an way of de novo assembly. Massive short-length reading data from the Illumina/Solexa system is enough to discover DNA variation, resulting in reducing the cost of DNA sequencing. Whole-genome expression profile data are useful to approach genome system biology with quantification of expressed RNAs from a whole-genome transcriptome, depending on the tissue samples. The hybrid mRNA sequences from Rohce/454 and Illumina/Solexa are more powerful to find novel genes through de novo assembly in any whole-genome sequenced species. The 20× and 50× coverage of the estimated transcriptome sequences using Roche/454 and Illumina/Solexa, respectively, is effective to create novel expressed reference sequences. However, only an average 30× coverage of a transcriptome with short read sequences of Illumina/Solexa is enough to check expression quantification, compared to the reference expressed sequence tag sequence.